PRODUKSI BERAS DAN KETERSEDIAAN SUMBER DAYA LAHAN PERTANIAN DALAM RANGKA MEMPERKUAT KEMANDIRIAN PANGAN DI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - SITI SYAMSIAR (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2013)
The one of development strategy and established of food self-sufficient in Daerah Istimewa Yogyakarta (DIY) Province is using food ( rice ) production capacitydevelopment that related with optimize of the using of land resources. This effort has a opportunity to success remind that land resources in DIY has wet land as wide 56.538 hectare and dry land as wide as 262.042 hectare, also un use shore land that can be use for agriculture activities.